PELANGGARAN HAK MORAL ATAS KARYA CIPTA DALAM PENERBITAN ELEKTRONIK - IMAS ROSIDAWATI WIRADIRJA (Jurnal Litigasi, 2016)
Moral Rights protection is getting ignored in the era of global economy, specially since the beginning the emergence of the Information Technology revolution is marked by the use of the Internet as a means of communication. In the era when copyrights exploitation is becoming more intensive, complex, and multifacet, the appreciation of moral rights is being ignored. Society can access easily in the form of information products and other digital products which can be directly received. However, copyright infringement for e-books are often overlooked, because it's so easy to copy and modify digital product. Issues related to moral rights are the work of the e-book is translated without permission, and then up loaded in the Internet. This is an issue that occurs in cyberspace. Copyright is the legal protection extended to the owner of the rights in an original work that he has created on e-book. Nowadays, people can easily access and obtain digital information such as e-book which is published and reproduced without respecting the copyrights of it. The issue related to the moral rights is that the e-book is translated without getting legal permission from the author, and publish it on the internet. This is a law issue in the realm of internet. Copyrights privides legal protection to the original owner of the e-book. That is why; the objective of this study is to find and analyze copyrights breaching happens in cyberspace and what efforts needed to examine prevention of moral rights infringement under Indonesia regulations.